Antioxidant activities of Rapana venosa meat and visceral mass during simulated gastrointestinal digestion and their membrane ultrafiltration fractions. (15th September 2017) - Luo, Fenglei; Xing, Ronge; Wang, Xueqin; Yang, Haoyue; Li, Pengcheng
Summary: Rapana venosa ( Rv ) is an abundant marine snail resource with high content of protein. The antioxidant activities of Rv meat and visceral mass during simulated gastrointestinal (GI) digestion and their membrane ultrafiltration fractions were evaluated. Results indicated that visceral mass possessed stronger antioxidant activities than meat. The simulated GI digestion increased the hydroxyl radical scavenging activity while decreased the 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) scavenging activity and reducing power. After membrane ultrafiltration, there were three fractions, that is molecular weight (MW) > 10 kDa, MW 3.5–10 kDa and MW < 3.5 kDa. Fractions with MW > 10 kDa and MW < 3.5 kDa showed the highest hydroxyl, DPPH radical scavenging activity, respectively. Fractions with MW 3.5–10 kDa and MW > 10 kDa showed the highest reducing power for meat and visceral mass, respectively. Rv hydrolysates exhibited significantly higher hydroxyl radical scavenging activity than the positive control vitamin C (Vc) and may serve as useful ingredients for application in food industry nutritional products. Abstract : After simulated gastrointestinal digestion, most Rapana venosa proteins were hydrolyzed and their hydroxyl radical reducing activity was enhanced, which was higher than vitamin C. The hydrolysates with different molecular weight showed different antioxidant activities.